Transformasi Historis Paradigma Peradaban Besar terhadap Perempuan - Udin Saprudin (Lembaga Yasin AlSys, 2025)
This article analyzes the historical transformation of major civilizational paradigms concerning women, with a focus on the pre-Islamic period and the fundamental changes introduced by Islam. The main problem examined is how social, legal, and cultural constructions in various civilizations positioned women in a subordinate status, and the extent to which Islam corrected and revised these paradigms. The study employs a qualitative method with a library research design, using a historical-descriptive approach and textual analysis of classical sources, religious texts, and contemporary scholarship on gender in Islam. The findings show that in many civilizations, including pre-Islamic Arabia, women experienced discrimination in social, economic, and political spheres and were often reduced to objects and commodities. The prophetic mission of Prophet Muhammad shallallāhu ‘alaihi wasallam marked a paradigmatic turning point, as the Al-Qur’an presented a new framework that recognizes women as dignified subjects, bearers of spiritual, social, and legal rights, and partners with men in building civilization. Thus, Islam offers a normative correction to earlier patriarchal paradigms and establishes a universal foundation for gender justice. The implications of this study underscore the contemporary relevance of Islam’s normative values for re-reading discourses on women in the modern era and provide an ethical reference for efforts to realize a more just, inclusive social order grounded in gender justice.